Gains and losses within the homeless service, supportive housing, and harm reduction sectors during the COVID‐19 pandemic: A qualitative study of what matters to the workforce. (6th September 2022) - Goodwin, Jordan M.; Tiderington, Emmy; Kidd, Sean A.; Ecker, John; Kerman, Nick
Abstract: The COVID‐19 pandemic has had deleterious effects on individuals experiencing homelessness; yet, less is known about how this global health crisis is impacting service providers that support the homeless population. This qualitative study examined the perceived impacts of the COVID‐19 pandemic on the lives and work experiences of service providers in the homeless service, supportive housing, and harm reduction sectors in Canada. Further analyses were conducted to identify the occupational values that were represented in the work‐related changes experienced by providers. A stratified purposive sample of 40 participants (30 direct service providers and 10 providers in leadership roles) were drawn from a pan‐Canadian study of the mental health of service providers working with individuals experiencing homelessness. Reflexive thematic analysis was used to identify five themes of the work‐related changes experienced by service providers during the pandemic: [1] "Everything was changing every day" : Work role and responsibility instability ; [2] "How on Earth do we do our job?" : Challenges to working relationships with service users ; [3] "It used to be a social environment" : Transitions to impersonal and isolating workspaces ; [4] "It all comes down the chute" : Lack of organisational support and hierarchical conflict ; and [5] "We've been supported as well as we could have" : Positive organisational support and communication . The findings underscored how many of the occupational changes during the pandemic did not align with service providers' occupational values for collaboration, control, effective and safe service provision, and the importance of human relationships, among other values. As pre‐existing sectoral problems were exacerbated by the pandemic, recovery efforts need to address these long‐standing issues in ways that are aligned with service providers' values. Future research is warranted on how organisational approaches can promote supportive workplaces for service providers and improve outcomes for individuals experiencing homelessness.